Completely monotone functions on lie semigroups - Mirotin, A. R. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We obtain an integral representation of a completely monotone function on a Lie semigroup and prove the equivalence of “difference” and “differential” definitions of this function.